Examining strategies for improving healthcare providers' communication about adolescent HPV vaccination: evaluation of secondary outcomes in a randomized controlled trial. Issue 7 (3rd August 2019) - Reno, Jenna E.; Thomas, Jacob; Pyrzanowski, Jennifer; Lockhart, Steven; O'Leary, Sean T.; Campagna, Elizabeth J.; Dempsey, Amanda F.
ABSTRACT: There is a critical need for campaigns and interventions to increase rates of human papillomavirus (HPV) vaccination among U.S. adolescents. Healthcare providers are key stakeholders in parents' HPV vaccine decision-making. The current study presents the evaluation of secondary outcomes in a multi-component communication-based intervention to improve healthcare providers' communication about HPV vaccination. Evaluation was conducted via surveys of providers participating in a 12-month randomized controlled trial. Findings suggest use of communication components (combined use of the presumptive approach [PA] with all patients, and motivational interviewing and a fact sheet with vaccine hesitant parents) contributed to providers in the intervention group reporting higher perceived levels of parental HPV vaccine acceptance than control providers, as well as increased vaccination rates in the intervention arm in the main RCT.